2008
DOI: 10.1007/s00192-008-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, abuse and its relationship to interstitial cystitis

Abstract: This study evaluated the prevalence of depression, sexual abuse, and physical abuse among women diagnosed with interstitial cystitis (IC). One hundred forty-one subjects completed the validated Beck's Depression Inventory II Questionnaire (BDI-II) and the validated Drossman Abuse Questionnaire. Ninety-seven (69%) subjects scored 14 or higher on the BDI-II, corresponding to depression. When compared to the US prevalence of 9%, this was significantly higher. Fifty-one subjects (36%) reported sexual abuse which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
3
40
0
1
Order By: Relevance
“…These findings from a community-based sample are consistent with reports from clinical populations that compare rates to healthy controls[2]. The prevalence of urological symptoms among the twins was 7.8%, falling within the limits of previously reported estimates from community studies of women[24-26].…”
Section: Discussionsupporting
confidence: 89%
“…These findings from a community-based sample are consistent with reports from clinical populations that compare rates to healthy controls[2]. The prevalence of urological symptoms among the twins was 7.8%, falling within the limits of previously reported estimates from community studies of women[24-26].…”
Section: Discussionsupporting
confidence: 89%
“…[1, 1214] The prevalence of panic disorder co-morbid with BPS/IC has been estimated at 14 %, [1] although studies linking the related problem of irritable bowel syndrome to panic disorder have found panic rates of co-morbidity as high as 46 %. [15] These studies focused on patient samples and therefore the population prevalence of BPS/IC symptoms and co-morbid depression or panic is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[7, 9, 1622] Among patients being treated for pain conditions, depression is associated with more pain complaints, worse pain, longer duration of pain, and a greater likelihood of non-recovery. [4, 12] Among patients with depression, pain is associated with a delay in diagnosis and treatment, more severe depression, functional limitations, and worse health-related quality of life. Pain has a strong, negative impact on both the recognition and treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Patients reporting concomitant pain and depression have a reduced likelihood of recovery and longer symptom duration. 23 With depression estimates in IC/BPS varying from 5% to greater than 50% of samples, 12,24,25 and pain as a cardinal symptom, 2 identification of SI in tertiary care is recommended. Although depression in this study has a stronger association with SI than catastrophizing, depression and catastrophizing likely manifest in tandem.…”
mentioning
confidence: 99%